Att förhålla sig till den nära historien - Sunding, Anna (2009)
This thesis concerns the term contemporary history and its role in landscape architecture. Today's contemporary history is defined as the planning and architecture connected to the 60s and 70s, in Sweden carried out as a large scale planning project called "Miljonprogrammet", which set out to build one million new residences in ten years. Initially, the term contemporary history and its complex of problem are examined. To deepen the picture of today's situation, a historical review has been made, starting in early 1900s ending in 2000s concerning how different planning and architectural influences has varied through the years. A rendering concerning how the view of the contemporary history has been and if there are structures and opinions repeating over time. The result of the review is that not many are neutral in the depiction of the 60s and 70s planning and architecture. There seems to be a bias that is not always in close connection to reality. This is partly explained by the picture that media has contributed to since these areas where newly built; a consistently negative picture that gradually has become the truth. In the research, a pendulum effect has also been identified concerning the ideals of planning and architecture. The shift has been between a traditional view which emphasise historical anchoring and a modern view that stresses new materials and building techniques. Depending on which view is the current, the other is being criticised and adjusted in greater or lesser extent. Deriving from this, a discussion on how the areas of the "Miljonprogram" can be seen in present day not as a mistake in planning and architectural history, but rather a cultural-historical event that demands to be evaluated according to its on premises. Further, the discussion shows how we in many ways reason as in the 60s where you tried to correct what was considered mistakes, and create a new timeless style by removing or recreating areas that doesn't fit the picture. Finally a discussion is held on how it is possible to deepen the understanding on the described pendulum effect by introducing the term contemporary history in the field of landscape architecture and by that create a more sustainable view on urban planning.